1999
DOI: 10.1046/j.1432-1327.1999.00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of microsomal glutathione transferase 1 in mammalian tissues

Abstract: An extensive Northern blot analysis of microsomal glutathione transferase 1 in human and rat tissues was performed. When normalized against the glyceraldehyde‐3‐phosphate dehydrogenase or actin expression it was evident that the predominant expression occurs in liver and pancreas. An ontogenetic, as well as a functional, basis for the high levels in these two organs is possible. The relative expression levels in man ranged from: liver and pancreas (100%), to kidney, prostate, colon (30–40%), heart, brain, lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 26 publications
3
13
0
Order By: Relevance
“…This observation, together with subsequent work, has firmly established the concept that microsomal glutathione transferase 1 (MGST1) activation occurs with a large variety of electrophiles (of which some are reactive intermediates). During the last 20 years, MGST1 has been extensively studied regarding gene structure (Kelner et al, 1996(Kelner et al, , 2000Iida et al, 2001), organ and species distribution (Estonius et al, 1999), molecular properties (Morgenstern et al, 1982(Morgenstern et al, , 1988Weinander et al, 1997;Svensson et al, 2000), three-dimensional structure (Schmidt-Krey et al, 2000), regulation (Andersson et al, 1994), and mechanism (Morgenstern et al, 2001). Recently, MGST1 has been grouped in a new superfamily named membrane-associated proteins in eicosanoid and glutathione metabolism (MAPEG) (Jakobsson et al, 1999a), which is involved not only in xenobiotic metabolism and cellular protection but potentially also in pain, fever, inflammation, cancer, apoptosis, allergy, and asthma (Jakobsson et al, 1999b;Funk, 2001).…”
Section: Glutathione Transferasementioning
confidence: 99%
“…This observation, together with subsequent work, has firmly established the concept that microsomal glutathione transferase 1 (MGST1) activation occurs with a large variety of electrophiles (of which some are reactive intermediates). During the last 20 years, MGST1 has been extensively studied regarding gene structure (Kelner et al, 1996(Kelner et al, , 2000Iida et al, 2001), organ and species distribution (Estonius et al, 1999), molecular properties (Morgenstern et al, 1982(Morgenstern et al, , 1988Weinander et al, 1997;Svensson et al, 2000), three-dimensional structure (Schmidt-Krey et al, 2000), regulation (Andersson et al, 1994), and mechanism (Morgenstern et al, 2001). Recently, MGST1 has been grouped in a new superfamily named membrane-associated proteins in eicosanoid and glutathione metabolism (MAPEG) (Jakobsson et al, 1999a), which is involved not only in xenobiotic metabolism and cellular protection but potentially also in pain, fever, inflammation, cancer, apoptosis, allergy, and asthma (Jakobsson et al, 1999b;Funk, 2001).…”
Section: Glutathione Transferasementioning
confidence: 99%
“…The microsomal GST has been localized to the endoplasmic reticulum, the outer mitochondrial membrane, and the plasma membrane (Morgenstern et al, 1984;Horbach et al, 1993). The rat microsomal GST has a high degree of sequence similarity to the human microsomal GST, and although it is found predominantly in the liver, in both human and rat, the enzyme is extensively distributed in extrahepatic tissues (Otieno et al, 1997;Estonius et al, 1999). In addition to catalyzing typical conjugation reactions with GSH, the microsomal GST possesses selenium-independent glutathione peroxidase activity and catalyzes the reduction of phospholipid hydroperoxides (Mosialou and Morgenstern, 1989), and it has been suggested that activation of the microsomal GST under conditions of oxidative stress may protect cells from oxidative damage (Mosialou and Morgenstern, 1989;Aniya and Anders, 1992).…”
mentioning
confidence: 99%
“…Similarly, in humans, MGST2 is expressed in the liver and small intestine (Jakobsson et al, 1996), and MGST3 is expressed in heart (Jakobsson et al, 1997). Cynomolgus MGST1 is expressed in the liver, jejunum, and kidney (Uno et al, 2009), similar to human MGST1 (Estonius et al, 1999). The results indicate similarities between cynomolgus macaque and human MGST tissue expression patterns.…”
Section: Resultsmentioning
confidence: 69%